2019
DOI: 10.11646/phytotaxa.397.4.2
|View full text |Cite
|
Sign up to set email alerts
|

Two new species of Hechtia (Bromeliaceae, Hechtioideae) from Oaxaca, Mexico

Abstract: Hechtia gypsophila and H. minuta, two new species from Oaxaca, Mexico are described and illustrated. The proposed species are compared with H. pumila, taxon that present some similarities and also with other species that grow near the type localities of the two new taxa proposed. Images and a distribution map of all taxa are included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…In recent years, efforts have been made to determine the evolutionary history of this group of plants by analyzing their phylogenetic relationships and the description and delimitation of their species (García-Ruiz et al 2014, González-Rocha et al 2014, López-Ferrari & Espejo-Serna 2014a, Ramírez-Morillo et al 2014, Ramírez-Morillo et al 2015, Ramírez-Morillo et al 2016, Flores-Argüelles et al 2019, Hernández-Cárdenas et al 2019, Hernández-Cárdenas et al 2020, Romero-Soler et al 2022). These advances have made possible to identify the monophyly of Hechtioideae and the presence of three well-supported clades corresponding to three genera; Bakerantha with five species, Hechtia with ca.…”
mentioning
confidence: 99%
“…In recent years, efforts have been made to determine the evolutionary history of this group of plants by analyzing their phylogenetic relationships and the description and delimitation of their species (García-Ruiz et al 2014, González-Rocha et al 2014, López-Ferrari & Espejo-Serna 2014a, Ramírez-Morillo et al 2014, Ramírez-Morillo et al 2015, Ramírez-Morillo et al 2016, Flores-Argüelles et al 2019, Hernández-Cárdenas et al 2019, Hernández-Cárdenas et al 2020, Romero-Soler et al 2022). These advances have made possible to identify the monophyly of Hechtioideae and the presence of three well-supported clades corresponding to three genera; Bakerantha with five species, Hechtia with ca.…”
mentioning
confidence: 99%
“…The prevalence of the order Fabales also may be due to adaptations such as the capacity to accumulate Ca and S or form a symbiosis with Rhizobium Frank that provide We were surprised that species of Hechtia (Bromeliaceae) and Bletia (Orchidaceae) may be potential gypsophytes, as their families consist largely of epiphytic species and orchids that have not been previously reported in gypsum soils in Campeche. However, gypsophytes from both genera have been found in the state of Oaxaca (Hernández-Cárdenas et al 2019;Salazar et al 2016), andMusarella et al (2018) reported gypsovags from Orchidaceae in a checklist of gypsophilous vascular flora in Italy. Contrary to the assumption of Martínez and Galindo-Leal (2002), the Sapotaceae family was poorly represented (two species).…”
Section: Vascular Plant Diversity In Gypsum Outcrops Of Campechementioning
confidence: 99%